The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1093/oxfordjournals.aje.a116850
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Sports Activity as Determinants for Age at Menarche

Abstract: A prospective study (1985-1991) was conducted to evaluate the role of nutrition, physical activity, and other life-style factors for the age at menarche, a known breast cancer risk factor. In 1988-1989, a total of 261 girls, aged 8-15 years, from a nationwide representative nutrition and activity survey (1985-1988) responded additionally to a mailed questionnaire on personal maturation and anthropometric data, physical activity, and information about nutritional habits, measured by a short food-frequency quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
139
2
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 0 publications
6
139
2
3
Order By: Relevance
“…A large retrospective study of UK vegetarians in the 1990s found no difference in AAM between life-long vegetarians and those becoming vegetarian as adults (48) . Several other later studies which measured protein intake around the time of menarche found little evidence of an association (10)(11)(12)(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 90%
“…A large retrospective study of UK vegetarians in the 1990s found no difference in AAM between life-long vegetarians and those becoming vegetarian as adults (48) . Several other later studies which measured protein intake around the time of menarche found little evidence of an association (10)(11)(12)(13)(14)(15) .…”
Section: Discussionmentioning
confidence: 90%
“…4 High levels of moderate and vigorous physical activity before menarche may delay the onset of menses. 25,26 During a woman's reproductive years, strenuous exercise activity is associated with an increased likelihood of secondary amenorrhea, irregular or anovulatory menstrual cycles, and shortened luteal phases of the menstrual cycle. 27,28 These alterations in menstrual function have been associated with reduced levels of estradiol, progesterone, and follicle-stimulating hormone, particularly during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that the alteration of eating patterns as a result of rationing in the wartime and immediate post-war period, and the subsequent influence on certain breast cancer risk factors probably produced by such changes (e.g. age at menarche; Merzenich et al, 1993) coupled with the introduction of the United Kingdom National Health Service in 1948 and the subsequent availability of cod liver oil, orange juice and milk formulate for all infants and young children, and school milk for school-age children, may be having some influence on the development of healthier girls and women. Such speculation could be addressed in a well-designed epidemiological study.…”
Section: Discussionmentioning
confidence: 99%